A new species and taxonomic notes on Lycianthes series Glanduliferae (Solanaceae) from the Brazilian Amazon - Costa-Silva, Rafael; Giacomin, Leandro Lacerda; Agra, Maria De Fátima (Phytotaxa, 2021)
During our analyses of Lycianthes exsiccates, as part of the taxonomic treatment for the Brazilian flora, a new species was discovered and is described and illustrated here. The species is compared and contextualized within the infra-generic classification of Lycianthes. Analyses of indument and trichomes were performed by stereomicroscopy (SM) and scanning electron microscopy (SEM). The new species, Lycianthes amazonica, is recognized as an endemic species to the Brazilian Amazon, which has its habitat described as secondary formations (capoeira) of terra-firme forests. It is closely related to L. sprucei, with which shares the scandent or vine habit, flexuous branches and ferrugineous indument of glandular trichomes. However, they are distinguished by several morphological features, including trichomes morphology, a sessile inflorescence and calyx appendages of equal length; both species belong to Lycianthes. subg. Polymeris sect. Eulycianthes ser. Glanduliferae. The description of this species expands the total number of Lycianthes species to the Brazilian Amazon to six, as well as thirteen to Brazil. The affinities of Lycianthes amazonica with its related species, distribution, ecology, and conservation status are discussed. Additionally, a lectotypification of Lycianthes sprucei, a species closely related to L. amazonica, is proposed.